Fluorescence spectroscopic and molecular modelling studies on the molecular interaction mechanism of bromodeoxyuridine with human serum albumin / Amira Adlin Roslan - Amira Adlin , Roslan (2020)
The interaction of a nucleoside analogue, bromodeoxyuridine (BrdU) with human serum albumin (HSA) was studied to investigate the binding phenomenon and analyze the protein conformation upon BrdU binding. Multiple spectroscopic techniques, viz. intrinsic and three-dimensional (3-D) fluorescence, ultraviolet-visible (UV-Vis) absorption and circular dichroism (CD) spectroscopy along with molecular docking were used. A decrease in the Stern-Volmer constant (Ksv) with the increase in temperature suggested BrdU-induced quenching of protein fluorescence as static quenching and thus implied BrdU−HSA complex formation. This was also supported by UV-Vis absorption spectral results, showing hyperchromism in the absorption spectrum of HSA upon BrdU addition. Intermediate binding affinity between BrdU and HSA was evident from the Ka values (2.49−3.97 × 104 M−1), while BrdU−HSA complex formation was driven by hydrophobic and van der Waals interactions along with hydrogen bonds, as revealed by thermodynamic data (ΔS = +28.48 J mol−1 K−1; ΔH = −17.16 kJ mol−1). The feasibility of the binding reaction was confirmed from the negative sign of ΔG values. The binding reaction was found to be exothermic in nature, as disclosed by the negative ΔH value, which also supported the decrease in the Ka value with increasing temperature. Minor changes occurred in both secondary and tertiary structures as well as in the fluorophores' microenvironment of HSA, as recognized from the CD spectral results in the far-UV and the near-UV regions and 3-D fluorescence spectra, respectively. Use of site markers (warfarin and indomethacin for the site I; diazepam for site II), as well as docking results, suggested BrdU binding to both site I (more preferred) and site II, located in subdomains IIA and IIIA, respectively, of HSA. A small but significant influence of several metal ions on the binding reaction between BrdU and HSA was also noticed.